Distinction of Jordan as a Destination for Religious Tourism - JAWABREH, Omar A.A. (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017DO - 10.14505//jemt.v8.6(22).03, 2018)
The purpose of this research study is to analyze Distinction of Jordan as a destination for religious tourism. This study was designed to establish a partnership between all tourism sectors in Jordan for the development of religious tourism to facilitate the operations of the exchange of information and ideas related to the development of tourism, several statistical measures were used such as arithmetic mean, test t, Cronbach's alpha test, and standard deviation, and ANOVA test. There is a relationship between the excellence of Jordan as a destination for religious tourism and the role of official agencies.